Agricultural Export and Overexploitation of the Ica Aquifer in Peru - Muñoz, Ismael (2016)
The economic growth experienced in the agricultural export sector in the Ica Valley has gone along with the concentration of land and groundwater sources. This process has given more power to the exporting companies, which respond individually to demand from international markets. The external demand increase of Ica valley’s products generates significant private gains, but inhibitscollective action towards the conservation of the aquifer. Each company decides the number of wells to be drilled and the volume of groundwater to be drawn, given the technical requirements of the crops and the weak government regulation. The increased extraction compared to the reserve and availability of water, leads to a decrease in the volume of water in the aquifer and to the degradation of the common and consequent scarcity.The research has followed the institutional economy approach to analyze the inter-relations between the social, the technological and the public policies in Ica’s Valley looking for an interdisciplinary perspective.